Takotsubo Cardiomyopathy following a L2–L5 Laminectomy and Fusion In Situ with Bone Morphogenic Protein. (27th March 2013) - Weaver, John; Eubanks, Jason
Abstract : Takotsubo cardiomyopathy (TC) is a rare, transient cardiomyopathy, with symptoms mimicking myocardial infarction. It has been reported to typically occur in postmenopausal women and is often triggered by an intense physical or emotional event with stimulation of the sympathetic response; the exact etiology, however, is uncertain. Bone morphogenic protein (BMP) is widely used in spinal fusions and has been associated with numerous perioperative complications. BMP is known to stimulate sympathetic pathways. In this paper, we present the case of a patient with a 7-hour episode of TC after a spinal fusion with bone morphogenic protein. The patient's symptoms resolved and long-term followup has been uneventful. This is the first paper to describe TC in the setting of spine or other major orthopaedic surgery and it suggests another possible area for further investigation in peri-operative events potentially associated with the use of bone morphogenic protein.